Manusia Gaib as The Translation of Invisible Man: Linguistic and Cultural Errors in Translating English Novel - Yulieda Hermaniar (STKIP PGRI Banjarmasin, 2016)
This study is aimed to describe the errors in linguistic and cultural aspect when Yuliani Liputo and Eva Y. Nukman translate Invisible Man into Manusia Gaib. Paragraphs that consist of errors in linguistic and cultural are taken and analyzed to gather the data. In collecting the data, the writer uses library research. It is conducted by collecting data from materials related to literature of the problem. There are 11 data that need to be observed by the writer. The writer compares the source language text and the target language text and gives her analysis about what errors occur and also the suggested translation for the errors. The data which have been observed by the writer show the errors that have been classified: (1) Linguistic; syntactical, morphological, and semantic. (2) Cultural errors; socio-culture. The data which have been observed by the writer show that the translator made errors in linguistic and cultural aspect. In translating the novel, the translator does not pay attention to linguistic and cultural aspects in the novel. Based on the data which have been analyzed, the writer found that in translating a novel, a translator needs to learn not only about all types of translation, but also the linguistic and cultural issues in the novel. In linguistic aspect, a translation should realize the differences between the source language and target language, pay attention to modifier, and classification of word. In cultural aspect, a translation should be aware of cultural issue in the novel